Zebrafish as a Model System for the Study of Severe CaV2.1 (α1A) Channelopathies - Tyagi, Sidharth; Ribera, Angeles B.; Bannister, Roger A. (Frontiers in Molecular Neuroscience, 2020)
P/Q-type CaV2.1 channel regulate neurotransmitter release at neuromuscular junctions and many central synapses. CACNA1A encodes the pore-containing 1A subunit of CaV2.1 channels. In humans, de novo CACNA1A mutations result in a wide spectrum of neurological, neuromuscular and movement disorders, such as familial hemiplegic migraine type 1, episodic ataxia type 2, as well as a more recently discovered class of more severe disorders which are characterized by ataxia, hypotonia, cerebellar atrophy and cognitive/developmental delay. Heterologous expression of CaV2.1 channels has allowed for an understanding of the consequences of CACNA1A missense mutations on channel function. In contrast, a mechanistic understanding of how specific CACNA1A mutations lead in vivo to the resultant phenotypes is lacking. In this review, we present the zebrafish as a model to both study in vivo mechanisms of CACNA1A mutations that result in synaptic and behavioral defects and to screen for effective drug therapies to combat these and other CaV2.1 channelopathies.